Paracardiac Gossypiboma (Textiloma) in 2 Patients - Mavioglu, Levent; Ertan, Cagatay; Mungan, Ufuk; Ozatik, Mehmet Ali (TEXAS HEART INST, 2015)
Gossypiboma, also called textiloma, results when a cotton matrix such as a gauze pad or surgical sponge is left in a body cavity after surgery. The diagnosis of gossypiboma can be challenging. In symptomatic patients, operative removal of the pad or sponge is recommended

however, the decision to operate might be less immediately clear in asymptomatic patients. We report the cases of 2 patients in whom we diagnosed paracardiac gossypiboma. In addition, we briefly review other cases and discuss the treatment of asymptomatic patients.
Keywords: Diagnosis, differential; foreign bodies/diagnosis/surgery; foreign-body reaction; medical errors/prevention \& control; postoperative complications/etiology; reoperation; surgical sponges/adverse effects; time factors; treatment outcome